The Influence of Customer Orientation, Promotion and Service on Customer Satisfaction - Uswatun Imania; Desy Bariyyatul Qibtiyah (Al-Qalam Institue, 2025)
This study aims to analyze the influence of customer orientation, promotion, and service on customer satisfaction from a sharia perspective. The research adopts a quantitative approach, involving 150 respondents who have purchased products either directly or online. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with the SmartPLS 4 software. The results reveal that customer orientation, promotion, and service each have a positive and significant effect on customer satisfaction. Furthermore, the findings underscore that incorporating Islamic principles such as honesty, responsibility, and quality service into business operations contributes to enhanced customer trust and satisfaction. Theoretically, this study supports the integration of Islamic business ethics in modern marketing strategies, demonstrating that sharia-compliant practices are not only spiritually aligned but also commercially viable. In an educational context, the findings provide valuable insights for business and economics educators, especially in Islamic higher education, to emphasize the relevance of ethical entrepreneurship and value-based service delivery. Teaching such approaches can foster the development of future business leaders who are both market-savvy and ethically grounded. This research highlights the strategic importance of aligning customer relationship management with faith-based values to achieve sustainable competitive advantage.